Injury risk is different in team and individual youth sport - Theisen, D.; Frisch, A.; Malisoux, L.; Urhausen, A.; Croisier, J. L.; Seil, R. (Journal of Science and Medicine in Sport, 2013)
Objectives This study compared sports injury incidence in young high-level athletes from various team and individual sports and investigated if sport participation patterns are linked to injuries. Design Prospective cohort follow-up. Methods Pupils from a public sports school (12-19 years) were recruited over two separate school years (2008-2009: 42 weeks, n = 199 athletes; 2009-2010: 40 weeks, n = 89 athletes). Training and competition volume and intensity were recorded via a personal sports diary. Sports injuries (time-loss definition) were registered by medical staff members using a standardized questionnaire. Results Injury incidence was significantly higher in team compared with individual sports (6.16 versus 2.88 injuries/1000 h, respectively), as a result of a higher incidence of both traumatic (RR = 2.17; CI95% = 1.75-2.70; p < 0.001), and overuse injuries (RR = 2.06; CI95% = 1.46-2.91; p < 0.001). A Cox proportional hazards regression revealed that team sports participation had a hazard ratio of 2.00 (CI95% = 1.49-2.68; p < 0.001) compared to individual sports, with additionally previous injury being a risk and age a protective factor. The number of competitions per 100 days was significantly higher in team sports, whereas the number of intense training sessions per 100 days was significantly lower. In team sports, the number of competitions per 100 days was positively associated with injuries (HR = 1.072; CI95% [1.033; 1.113]; p < 0.001), while in individual sports the number of competitions per 100 days had a protective effect (HR = 0.940; CI95% [0.893; 0.989]; p = 0.017). Conclusions Team sports participation entailed a higher injury risk, whatever the injury category. Further research should elucidate the role of characteristics related to sport participation in injury causation.